Adsorption of fibronectin onto polymethylmethacrylate and promotion of Staphylococcus aureus adherence. - Vaudaux, P E (1984)
Recent data suggest that fibronectin may favor Staphylococcus aureus infection by promoting attachment to either injured tissues or implanted foreign bodies. We studied the quantitative adsorption of fibronectin onto polymethylmethacrylate (PMMA) cover slips by using a 125I-labeled preparation of the purified plasma glycoprotein. Fibronectin in buffer solutions showed a high affinity to PMMA coverslips. Adherence of S. aureus Wood 46 was studied on PMMA pre-exposed to fibronectin, using an assay specifically adapted to the cover slip model. Whereas S. aureus adherence in an albumin-containing buffer was less than or equal to 10(3) CFU on control uncoated cover slips, adherence in the same medium increased up to maximum of 7.7 X 10(4) CFU on cover slips preincubated in a solution of fibronectin (125-micrograms/ml). At intermediate fibronectin concentrations, bacterial adherence was a linear function of both the quantity in solution and of the quantity adsorbed on the PMMA cover slips. The presence of human serum proteins, as represented by a fibronectin-depleted pool, essentially prevented adsorption of radiolabeled fibronectin on PMMA and subsequent bacterial adherence on the cover slips. Precoating of PMMA with denatured collagen resulted in increased fibronectin adsorption on PMMA, even in the presence of serum proteins, and S. aureus adherence was optimal on such surfaces. Collagen may therefore play a role as a cofactor contributing to S. aureus adherence onto fibronectin-coated substrata or foreign bodies.